The Role of Deep Learning in Improving English Language Acquisition - Qun Zhang; Aqsa Saleem; Gumarpi Rahis Pasaribu (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study explores the role of deep learning technologies in enhancing English language acquisition, focusing on how artificial intelligence-powered tools impact learners' development in listening, speaking, reading, and writing. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis across three educational settings where deep learning applications—such as speech recognition, automated writing feedback, and AI-driven chatbots—were actively used. The findings reveal that deep learning supports more personalized, adaptive, and autonomous learning experiences, with notable improvements in pronunciation, writing accuracy, vocabulary retention, and learner motivation. However, challenges such as technological limitations, unequal access, and insufficient teacher training were also identified. The study concludes that deep learning technologies hold significant potential as complementary tools in English language education, provided they are thoughtfully integrated into pedagogical frameworks. Implications for educators, policymakers, and future research are discussed.